Facile Synthesis of 7-Aryl-benzo[h]tetrazolo[5, 1-b]quinazoline-5, 6-dione Fused Polycyclic Compounds by Using a Novel Magnetic Polyurethane Catalyst. (27th May 2019) - Maleki, Ali; Aghaei, Morteza; Kari, Tooraj
ABSTRACT: Novel Brönsted acid functionalized magnetic polymeric nanocomposite, Ba0.5 Sr0.5 Fe12 O19 @PU-SO3 H, has been successfully synthesized and characterized by field-emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), vibrating sample magnetometer (VSM), Fourier transform infrared spectroscopy (FT-IR), energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM) and thermogravimetric analysis (TGA) techniques. The catalytic activity of the nanocomposite was tested in the regioselective synthesis of 7-aryl-benzo[h]tetrazolo [5, 1-b] quinazoline-5, 6-diones in an eco-friendly and recyclable media, deep eutectic solvent (DES), based on choline chloride and urea. This novel method offers several advantages, such as high yields, short reaction time, environmentally friendly reaction media, easy isolation of the product, and also offers an easy method for the synthesis of nanocatalysts. The catalyst was readily recycled by the use of an external magnetic field and could be reused 6 times without significant loss of activity or mass. DES as one of the most promising environmentally benign and cost-effective alternatives to conventional ionic liquids and volatile organic solvents was recovered from the aqueous filtrate by evaporating the water under vacuum. The recycled DES was used up to 4 runs without any loss in activity.